Activation of the Anti-Oxidative Stress Response Reactivates Latent HIV-1 Through the Mitochondrial Antiviral Signaling Protein Isoform MiniMAVS - Sarabia, Indra; Novis, Camille L.; Macedo, Amanda B.; Takata, Hiroshi; Nell, Racheal; Kakazu, Juyeon C.; Furler, Robert L.; Shakya, Binita; Schubert, Heidi L.; Hill, Christopher P.; DePaula-Silva, Ana Beatriz; Spivak, Adam M.; et al. (Frontiers in Immunology, 2021)
The mitochondrial antiviral signaling protein (MAVS) is part of the cell’s innate immune mechanism of defense. MAVS mRNA is bicistronic and can give rise to a full length-MAVS and a shorter isoform termed miniMAVS. In response to viral infections, viral RNA can be sensed by the cytosolic RNA sensors retinoic acid-inducible gene I (RIG-I) and/or melanoma differentiation-associated protein 5 (MDA5) and activate NF-B through interaction with MAVS. MAVS can also sense cellular stress and activate an anti-oxidative stress (AOS) response through the activation of NF-B. Because NF-B is a main cellular transcription factor for HIV-1, we wanted to address what role MAVS plays in HIV-1 reactivation from latency in CD4 T cells. Our results indicate that RIG-I agonists required full length-MAVS whereas the AOS response induced by Dynasore through its catechol group can reactivate latent HIV-1 in a MAVS dependent manner through miniMAVS isoform. Furthermore, we uncover that PKC agonists, a class of latency-reversing agents, induce an AOS response in CD4 T cells and require miniMAVS to fully reactivate latent HIV-1. Our results indicate that the AOS response, through miniMAVS, can induce HIV-1 transcription in response to cellular stress and targeting this pathway adds to the repertoire of approaches to reactivate latent HIV-1 in ‘shock-and-kill’ strategies.